Pendampingan Pengolahan Pisang Menjadi Produk Layak Jual di Dusun Arjoyoso Desa Ampegading Malang - Hosniyeh, Hosniyeh (Universitas Islam Internasional Darullughah Wadda'wah, 2024)
This service is located in Arjoyoso Hamlet, Ampelgading Village, Malang Regency. Arjoyoso Hamlet produces quite a lot of bananas, around 1000 each year. However, even though bananas are abundant, they are only used for direct consumption and sold as fresh fruit. Therefore, this mentoring program aims to provide training to the community, especially farmers and small businesses, about good banana processing techniques, starting from selecting raw materials, processing, to product packaging and marketing, in order to improve the community's economy. This service uses the PAR method, based on Maqoshid Al-Syari'ah, the stages in this service are: socialization, interviews, distributing questionnaires, and FGD with the surrounding community. Meanwhile, the instrument in this research is interviews. The results of this service include successfully obtaining a SK Banana Usaha Group, halal certificate, NIB and P-IRT legality. This product is called Champion Banana Chips with four flavor variants, namely Chocolate, Salted Onion, Sweet Spicy and Sweet Honey.